1985
DOI: 10.1159/000183539
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in Man with a Kidney Transplant: Role of Familial versus Other Factors

Abstract: Genetic factors are clearly involved in the pathogenesis of essential hypertension in man. In at least three rat models of genetic hypertension it is possible to transplant the hypertension with the kidney. To see whether or not the same is true for humans, we carried out a 2-year retrospective study of 50 selected recipients of a cadaver kidney. We correlated the following factors by multivariate statistical analyses: presence or absence of hypertension in the family of donor and recipients; donor’s and recip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…Thus, a generalized and genetically determined cellular defect involving faster Na transport across the renal cell membranes (19) was considered a probable cause of hypertension in MHS. Some of the erythrocyte and kidney dysfunctions seen in these rats have also been found in a subset (=25%) of human patients with primary hypertension (10,(20)(21)(22). In the rat model, the difference in membrane ion transport disappeared after elimination of the membrane skeleton, which indicated the involvement of some ofits components (23,24).…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Thus, a generalized and genetically determined cellular defect involving faster Na transport across the renal cell membranes (19) was considered a probable cause of hypertension in MHS. Some of the erythrocyte and kidney dysfunctions seen in these rats have also been found in a subset (=25%) of human patients with primary hypertension (10,(20)(21)(22). In the rat model, the difference in membrane ion transport disappeared after elimination of the membrane skeleton, which indicated the involvement of some ofits components (23,24).…”
mentioning
confidence: 70%
“…This work demonstrates an interaction between two independently segregating genes determining the expression of a single protein that is involved in inheritance ofprimary hypertension. Considering the many similarities in kidney and cellular dysfunctions between MHS and subsets of patients with primary hypertension (10,(20)(21)(22) and the very high degree of sequence homology between rat and human adducin (data not shown), it is possible that these molecular mechanisms are also relevant to humans.…”
Section: Resultsmentioning
confidence: 99%
“…Two other studies took the opposite approach by showing that grafts from donors with presumed hypertension 4 or from donors with known family background of essential hypertension 2 caused more severe hypertension and the need for more rigorous antihypertensive treatment in the recipients. The results of one of these studies 2 were later confirmed by a long-term historic prospective follow-up. 3 …”
mentioning
confidence: 75%
“…Many studies on essential HTN have implicated the kidney's ability to excrete sodium and maintain extracellular fluid volume as key elements in the pathogenesis of systemic HTN. In both rat [20] and human [21,22] models cross transplant of a kidney from a hypertensive donor to a normotensive host results in the development of HTN in the recipient thus implicating the kidney as the culprit [18]. Hypertension in CKD is associated with increased peripheral vascular resistance, major mechanisms responsible for this include activation of neurohormonal systems and increased arterial wall stiffness.…”
Section: Pressure Overloadmentioning
confidence: 99%